High‐throughput metabolic profiling based on small amount of hepatic cells. Issue 18 (30th May 2017) - Zhou, Lina; Yin, Peiyuan; Luo, Ping; Tang, Ling; Wang, Zhichao; Gao, Peng; Piao, Hailong; Lu, Xin; Xu, Guowang
Abstract: Common metabolomics platforms require about 10 6 cells, which has a limited throughput due to the time‐consuming steps of cell culture and preparation. There is a demand for metabolic profiling methods to improve analytical throughput and detection sensitivity based on small amount of cells. In this study, we proposed a high‐throughput scheme, integrating 96‐well plate cell cultivation, in‐situ cell pretreatment, and sensitive dansylation labeling coupled with LC‐MS analysis of metabolites inside HepG2 cells (of the order of magnitude of 10 3 cells in each well). A simple and rapid cell pretreatment was performed showing good extraction efficiency and good precision (the RSDs smaller than 5%) for polar metabolites. The recovery in metabolite extraction evaluated with three isotope‐labeled amino acids was from 89.7 to 106.3% at low, medium, and high concentrations. The suitability of the method was illustrated by exploring influences of different fatty acids on HepG2 cells.